Spectrophotometric Determination of Nirite By The Diazotization Coupling With Aniline and 4,6 Dihydroxy-2 Mercaptopyrimidine - Mohammed, H. J.; Hassan, D.S.; Hmood, A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A direct  spectrophotometric method  has  been  developed  for  thedetermination of nitrite  in aqueous  solution.  The method  is based on the  reaction  of  the nitritw  ion with an acidified  anline  solution from diazonium  cation   , which   is   subsequently  coupled   Â·with  4,6   - dihydroxy- 2- mercapto  pyrimidine to from yellow colored  and water- soluble  intense  azo dye  with maximum  absorption at  416nm  . Agraph  of  absorbance  versus  concentration  shows   that  Bee's  Lawsobeyed  over  the  concentration rang of 20 -100  ug of  nitrite  in final3volume  of  ml(i.e.,  2-10 ppm) with a molar absorpitivity of (3.5x  100.12j.lg.cmÂ· ) L.mole" 1  .cm"1) >a Sandall  sensitivity  of (                   2  , a relative error of  (-0.05%)  (-0.65%) and  a relaLive standard  deviation (0,&6-1.0%)depending  on the concentration.